The Influence of Product Quality and Price on the Sales of Photo Frames at the Printing House of CV. Multi Prinz in Gowa Regency - Nurul Fahri (www.amertainstitute.com, 2021)
This research aims to identify the influence of product quality and price on sales at Multi Prinz Gowa Printing. Using quantitative methods, this research involved 110 respondents as research samples. Data was collected through questionnaires, and data analysis was carried out using multiple linear regression tests. At the analysis stage, this research found significant results. First, product quality has a positive and significant influence on sales at CV Printing. Multi Prinz Gowa. This shows that consumers tend to be more interested in buying photo frames from the printer if the product offered is of good quality. Good quality can include aspects such as frame strength, image sharpness, and print cleanliness. Second, price was also found to have a positive and significant influence on sales at Multi Prinz Gowa Printing. This shows that competitive prices or according to the value offered can increase consumer purchasing interest. However, prices that are too high can also reduce purchase interest, so pricing must take into account product value and consumer preferences. Thus, these findings provide valuable insight for the management of Multi Prinz Gowa Printing in planning marketing strategies and pricing their photo frame products. By paying attention to product quality and competitive prices, this printing company can increase its competitiveness in the market and gain sustainable advantages